2013
DOI: 10.1063/1.4801394
|View full text |Cite
|
Sign up to set email alerts
|

Phase-delayed laser diode array allows ultrasonic guided wave mode selection and tuning

Abstract: (2013). Phase-delayed laser diode array allows ultrasonic guided wave mode selection and tuning. Journal of Applied Physics, 113 (14) Selecting and tuning modes are useful in ultrasonic guided wave non-destructive testing (NDT) since certain modes at various center frequencies are sensitive to specific types of defects. Ideally one should be able to select both the mode and the center frequency of the launched waves. We demonstrated that an affordable laser diode array can selectively launch either the S 0 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…We showed that phased photo-acoustic excitation permits tunable and selective mode excitation in coated tube samples, in a manner similar to that we used previously with free plate samples (Karppinen et al, 2013). In coated tubes we observed, within the frequency range of interest, several modes separated into five zones, whereas in the plate, there were only two modes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We showed that phased photo-acoustic excitation permits tunable and selective mode excitation in coated tube samples, in a manner similar to that we used previously with free plate samples (Karppinen et al, 2013). In coated tubes we observed, within the frequency range of interest, several modes separated into five zones, whereas in the plate, there were only two modes.…”
Section: Discussionsupporting
confidence: 84%
“…The illuminated spot on the coating was 2 mm in diameter. The laser diodes were successively excited using a tunable time delay, that is, phase delay (t pd ) (Karppinen et al, 2013). The fiber head (distance to the coating 2 mm) was translated along the long axis of the sample, in 0.5 mm steps, to provide sixty source-receiver distances within 20-50 mm range.…”
Section: A Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate defect detection, one could use Lamb waves with a specific frequency and shape. This can be done by modulating the exciting signal spatially and/or temporally [33,34].…”
Section: Discussionmentioning
confidence: 99%